Evaluation of a universal hepatitis B vaccination program and antenatal screening for hepatitis B surface antigen: Results from a real-world study 2015–2016. Issue 48 (26th November 2021) - Netanel, Carmit; Ben-Aharon, Omer; Ben-Ari, Ziv; Chodick, Gabriel; Anis, Emilia; Magnezi, Racheli
Highlights: The Hepatitis B vaccination program is epidemiologically and economically justified. Vaccination coverage was 94% for the first and 89% for the third dose. Antenatal hepatitis B antigen (HBsAg) positivity prevalence was 0.2% Birth dose coverage was higher among newborns of HBsAg positive mothers. Higher HBsAg positivity rates were found among foreign born mothers. Abstract: Background and Aims: Universal vaccination against hepatitis B virus (HBV) in infancy was implemented in Israel in 1992. This population-based study aimed to evaluate the coverage rate and cost-benefit of the HBV vaccination program among infants in Israel and the Hepatitis B surface antigen (HBsAg) status in their mothers. Methods: Using the database of a health maintenance organization with 2 million members, we retrospectively identified, all the infants born in 2015–2016 and their mothers. Maternal data collected included age, ethnicity, country of birth and HBsAg status during pregnancy. HBV vaccination coverage among infants was calculated. A cost-benefit analysis of the HBV vaccination program was conducted based on the actual costs of HBV infection treatments in all HBsAg positive mothers. Results: Our cohort included 72, 792 mothers who gave birth to 77, 572 live infants. A total of 71, 107 (97.7%) mothers were screened for HBV during pregnancy, of them 124 (0.2%), who gave birth to 132 infants were HBsAg positive. HBV vaccination coverage rates were 94%, 93% and 89%, for the first, second and third dose, respectively. Birth dose coverage of 95% among infants born to HBsAg positive mothers was significantly higher compared to HBsAg negative or unscreened mothers (p < 0.001). The percentage of HBsAg positivity among mothers who were born in Israel, the Former Soviet Union or Ethiopia, were 0.1%, 0.8% and 5%, respectively (p < 0.001). Ethnic differences were not found between HBsAg positive and HBsAg negative mothers. Calculated benefit-to-cost ratios were 1.24:1 and 4.15:1, with and without antenatal HBsAg screening, respectively. Conclusions: The Israeli vaccination program against HBV infection is epidemiologically and economically justified. High coverage rates among infants born to HBsAg positive mothers reflect very good adherence to the vaccination program and antenatal screening. Higher HBsAg positivity rates among immigrant mothers identify a high-risk population for HBV infection.